2000
DOI: 10.1152/ajplung.2000.278.5.l1000
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and morphogenesis of murine fetal distal lung in an allograft model

Abstract: Neovascularization is crucial to lung morphogenesis; however, factors determining vessel growth and formation are poorly understood. The goal of our study was to develop an allograft model that would include maturation of the distal lung, thereby ultimately allowing us to study alveolar development, including microvascular formation. We transplanted 14-day gestational age embryonic mouse lung primordia subcutaneously into the back of nude mice for 3.5-14 days. Lung morphogenesis and neovascularization were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…Saccular stage-like changes were observed in 11 weeks post-engraftment as compared to 3 weeks in our study. The accelerated timing observed in the present study is comparable to the subcutaneous mouse allograft model, where E14.5 mouse fetal lungs required two weeks to differentiate to the saccular stage (Schwarz et al, 2000). On the other hand, both of these are in contrast to the renal subcapsular mouse allograft model (Vu et al, 2003), where timing of developmental stages of E12.5 mouse embryonic lungs closely follows that of in utero development.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Saccular stage-like changes were observed in 11 weeks post-engraftment as compared to 3 weeks in our study. The accelerated timing observed in the present study is comparable to the subcutaneous mouse allograft model, where E14.5 mouse fetal lungs required two weeks to differentiate to the saccular stage (Schwarz et al, 2000). On the other hand, both of these are in contrast to the renal subcapsular mouse allograft model (Vu et al, 2003), where timing of developmental stages of E12.5 mouse embryonic lungs closely follows that of in utero development.…”
Section: Discussionsupporting
confidence: 69%
“…Various xenograft models have been used extensively in cancer research to study mechanisms of carcinogenesis and the effects of different pharmacological agents on human tumor growth (Giovanella and Fogh, 1985;Malkinson, 2001), as well as in studies of transmission of infection in various tissues by pathogens (Howett et al, 1997;Howett et al, 1990;Howett et al, 1999;Kish et al, 2001;Kreider et al, 1985). With respect to lung embryogenesis, immunocompromised mice have been used to study whole organ lung development in mice (Schwarz et al, 2000;Vu et al, 2003), as well as lower (Groscurth and Tondury, 1982;Peault et al, 1994) and upper airway development in humans (Delplanque et al, 2000;Deutsch, 1997;Engelhardt et al, 1993;Filali et al, 2002;Pilewski et al, 1994;Puchelle and Peault, 2000). Allograft models have been used where whole embryonic mouse lungs were grafted into severe-combined immunodeficient (SCID) mice (Schwarz et al, 2000;Vu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have shown that very early in lung development pulmonary vessels are present and connected to the systemic circulation. The vasculature develops in close relation with the airways and is a rate-limiting factor in branching morphogenesis [2][3][4]. This implies that the pulmonary vasculature plays an important role in lung development.…”
mentioning
confidence: 99%